Analisis Pengaruh Pelatihan dan Sertifikasi terhadap Produktivitas Pekerja - Kodri, Irfa; Fitriani, Heni; Juliantina, Ika (MEDIA KOMUNIKASI TEKNIK SIPIL, 2018)
Worker productivity is an important part of the successful development of human resources and infrastructure building. One of the ways to improve workers’ productivity is using training and worker certification. Therefore, there is a need to analyze the effects of training and certification on worker productivity with case study lightweight brick and steel rods workers in some projects in Palembang. This study aims to analyze the productivity value of workers between certified trained workers (TS) and untrained noncertified workers (BTBS) in the field. Furthermore, comparisons were also conducted on productivity based on field survey and Indonesian National Standard (SNI). This paper also analyzed the significant factors that affect workers productivity in the field. This productivity appraisal used field observation methods and questionnaire. From the results of the study, it was concluded that the training and certification of the workforce greatly affected the worker’s productivity; but some of workers’ productivity of trained workers (TS) and untrained noncertified (BTBS) met the standards of SNI, some did not. This was due to the influence of other factors beyond training and certification of the productivity value of handyman. Furthermore, based on t test results, the factors that significantly affect the productivity of workers were the skills of labor (X1), work motivation (X2) and management (X4). Thus the available regression equation was Y =0,024 +0,332 X1 + 0,676X2 -  0,039X4 + e.